(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article examines the essence of innovative transmission mechanism-cyclical nature of uneven economic development. As the analysis of the research results shows the cyclical fluctuations of innovation activity as an essential characteristic of the national economy are in an unstable, uncertain and poorly intended environment saturated with endogenous and exogenous economic factors. The research defines the feasibility of the study of the manifold economic pulse, the pulse of demand and monetary and fiscal impulses which in varying degrees are responsible for most of cyclical fluctuations. The paper found that the economic impulses – an integral part of innovation development of economy, the effects of which are spread by multiple transmission channels, it is one of the key macroeconomic variables to assess the current competitive situation of the country, as well as a long-term cyclical innovative development. It is also confirmed that the current wave-like fluctuations in economic activity in developed countries are able to synchronize to the lifting stage. The study needed highlight certain aspects of the theory of recurrence, as well as the different approaches of economic analysis of the impact of pulses on the innovative development of the economy. The study of sources of innovation impulses come to the conclusion that innovation impulses must be carefully considered in the analysis of the causes of cyclical fluctuations in the economy. There was a need to improve the innovation and the transmission of qualitative changes in the system of economic modernization. The research revealed that the transmission mechanism is cyclical and innovative development may be the most reliable basis for the formation of science-based ideas about the long-term prospects for economic development.